Moringa oleifera seed ethanol extract and its active component kaempferol potentiate pentobarbital-induced sleeping behaviours in mice via a GABAergic mechanism - Wei-Liang Liu; Bai-Fen Wu; Jian-Hua Shang; Xue-Feng Wang; Yun-Li Zhao; Ai-Xiang Huang (Taylor & Francis Group, 2022)
Context Moringa oleifera Lam. (Moringaceae) (MO) is an important food plant that has high nutritional and medical value. However, there is limited information on whether its seeds can improve sleep.Objective This study investigated the effects of MO seed ethanol extracts (EEMOS) on sleep activity improvement and examined the underlying mechanisms.Materials and methods Male ICR mice were placed into six groups (n = 12) and treated as follows: Control (sodium carboxymethyl cellulose, 20 mL/kg), estazolam tablets (2 mg/kg), EEMOS (1, 2 g/kg) and kaempferol (1, 2 mg/kg). These samples were successively given intragastric for 14 d. Locomotor activity assay, pentobarbital-induced sleeping and pentetrazol-induced seizures tests were utilized to examine the sedative-hypnotic effects (SHE) of EEMOS.Results Compared with the control group, the results revealed that EEMOS (2 g/kg) and KA (2 mg/kg) possessed good SHE and could significantly elevate the levels of γ-aminobutyric acid and reduce the levels of glutamic acid in the mouse hypothalamus (p < 0.05). Moreover, SHE was blocked by picrotoxin, flumazenil and bicuculline (p < 0.05). EEMOS (2 g/kg) and KA (2 mg/kg) significantly upregulated the protein expression levels of glutamic acid decarboxylase-65 (GAD65) and α1-subunit of GABAA receptors in the hypothalamus of mice (p < 0.05), not affecting glutamic acid decarboxylase-67 (GAD67) and γ2-subunit expression levels (p > 0.05). Additionally, they cause a significant increase in Cl- influx in human cerebellar granule cells at a concentration of 8 µg/mL (p  <  0.05).Discussion and conclusions These findings demonstrated that EEMOS could improve sleep by regulating GABAA-ergic systems, and encourage further clinical trials to treat insomnia.